Structure and Formation of Anticyclonic Eddies in the Iceland Basin. Issue 8 (8th August 2018) - Zhao, Jian; Bower, Amy; Yang, Jiayan; Lin, Xiaopei; Zhou, Chun
Abstract: The Iceland Basin has the most energetic eddy activities in the subpolar North Atlantic. This study documents the structure for an anticyclonic eddy in the Iceland Basin using high‐resolution hydrographic and velocity observations. The eddy core waters have lens‐like structure with warm and salty features in the upper 1, 000 m. The eddy distorts the density surface by doming the upper isopycnals and deepening the ones near the permanent pycnocline. The eddy has a diameter of about 120 km with substantial barotropic component in the velocity profiles. One branch of the North Atlantic Current in the central Iceland Basin is superimposed onto the eddy, leading to asymmetric velocity structure. Satellite maps show that eddy first shows up over the western slope of the Hatton Bank and moves westward to the central Iceland Basin. The waters enclosed in the eddy core share the same properties with Subpolar Mode Waters. Similar anticyclonic eddies are also found in high‐resolution numerical model simulations, which is used to explore eddy formation. The model results reveal that the potential vorticity gradient prior to the eddy event change signs in both horizontal and vertical directions. This potential vorticity gradient structure meets the necessary condition for the barotropic and baroclinic instabilities. Further calculation of the energy conversions suggests that eddies extract mean potential energy from the large‐scale isopycnal slope and gain the mean kinetic energy in the upper ocean. Therefore, both barotropic and baroclinic instabilities are involved to support the eddy growth. Key Points: The anticyclonic eddy in the Iceland Basin has warm and salty subsurface waters in its core and substantial barotropic velocity One branch of the North Atlantic Current in the central Iceland Basin is superimposed onto the eddy, leading to asymmetric velocity structure The energy conversions estimated from model results suggest that both barotropic and baroclinic instabilities are involved to support the eddy growth